Moderating role of government support on relationship between cultural dimensions and Saudi women’s leadership effectiveness - Hamad, Al-Alajmi Rajeh (2017)
The underrepresentation of women in academic and administrative leadership roles is a global phenomenon. This study aimed to investigate the important factors that influence the effectiveness of women leadership in the context of Saudi universities. There are still many obstacles faced by academic women leaders in universities. Women leadership effectiveness is still a significant problem that affects higher education institutions and the community of KSA. Thus, this research investigated the impact of gender egalitarianism, assertiveness, and future orientation on women leadership effectiveness in the public universities by taking government support as a moderating variable. The population of this study, consisting of 2800 female leaders, were divided into five groups based on the geographic regions (East, West, Middle, North and South). This study used the geographical clusters sampling to select the universities, and random sampling to select women leaders from each geographical cluster. 500 questionnaires were distributed among the employees working in the higher education sector of KSA. 271 questionnaires were returned and were usable for analysis with a response rate of 54%. This study employed the Structural Equations Modeling Approach by using the Partial Least Squares (PLS) to analyse the data. The results revealed that gender egalitarianism, assertiveness and future orientation have significant positive impacts on leadership effectiveness. The value of this study lies in finding government support as a significant moderating variable for assertiveness and future orientation to enhance women leadership effectiveness in Saudi universities. Future studies may adopt and examine different variables like motivation, organizational, cultural and other variables to understand leadership effectiveness at the organization level. The higher education sector of any country is considered as an important sector which needs female leaders besides the male to concentrate on achieving their goals successfully.